The answer to 1 is (E) All of the above. This is because a negative cannot be under a square root and it comes out as an i.
The answer to 2 is (B) a is real and b is imaginary. This is because anything that has an "i" attached to it is considered imaginary.
Y= a(x-3)^2+6
2= a(0-3)^2+6
2=a(-3)^2+6
2=a(9)+6
2-6=9a
-4=9a
-4/9=a
Therefore the equation in vertex form is
y = -4/9 (x-3)^2+6
Answer:
180/147
Step-by-step explanation:
We need to find the additive inverse of the given numbers.
- For finding it we may simply out -1 as multiplication in front of the terms .
<u>SOLUTION</u><u> </u><u>1</u><u> </u><u>:</u><u>-</u>
→ 3/-7 - 11/21
→ -3/7 -11/21
→ 3×-3 - 11 /21
→ -9-11/21
→ -20/21
<u>SOLUTION</u><u> </u><u>2</u><u> </u><u>:</u><u>-</u><u> </u>
→ 9/5 ÷ 7/5
→ 9/5 × 5/7
→ 9/7
→ Product of nos . = -20/21 × -9/7
→ Ans = 180/147
The answer is 3f
<span>=<span><span>18f</span>+<span>−<span>15f</span></span></span></span><span>=<span>(<span><span>18f</span>+<span>−<span>15f</span></span></span>)</span></span><span>=<span>3<span>f</span></span></span>
Write out the governing equation:
y = kx.
Take any point from the given table. You haven't shared the table, so I will invent a point: (2, 9).
Then find k: k = 9/2 Then the equation becomes y = (9/2)x.
Now let x = 7 and find y: y = (9/2)(7) = 63/2
Answer: y = 63/2